Hot melt adhesive composition
Patent Information
- Application Number
- JP2022536721
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-17
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing hot melt adhesive compositions used in disposable hygiene products face challenges in maintaining strong peeling strength and adhesiveness at high temperatures, particularly above 50°C, which is crucial for products transported and stored in hot climates, and they often fail to provide a good compromise between these properties over extended periods.
A hot melt adhesive composition comprising a specific co-polymer blend with controlled crystallization enthalpy and needle penetration, along with an adhesive resin, is formulated to maintain initial peeling strength and adhesiveness at high temperatures, using a combination of co-polymers A and B with defined needle penetration and crystallization enthalpy, and an adhesive resin within a specific weight percentage range.
The composition achieves improved peeling strength and adhesiveness over time, even at elevated temperatures exceeding 50°C, ensuring durability and performance stability for at least three weeks.
Abstract
Description
[Technical Field]
[0001] The present invention relates to a hot-melt adhesive composition comprising a specific combination of (co)polymers.
[0002] The present invention also relates to the use of the above-mentioned hot-melt adhesive composition. [Background technology]
[0003] Disposable sanitary products are made from a wide variety of substrates (nonwoven fabrics, elastomers, films, such as polyolefin films, especially polyethylene or polypropylene films) bonded together with adhesive materials. Examples of disposable sanitary products include diapers, napkins, or adult incontinence disposable products. Disposable sanitary products are manufactured at high line speeds. In such manufacturing, hot-melt adhesives are typically used because they can be easily applied to the substrate (in a molten state) without requiring additional manufacturing steps such as solvent removal, and they can rapidly form a strong bond upon cooling.
[0004] In general, several types of hot-melt adhesives can be found in disposable sanitary items, depending on their application and final function, as follows: -Core adhesive: Used not only during the manufacturing of diapers, but mainly during the use of diapers after they have become wet, to hold the core portion of the diaper (fluff and Super Absorbent Polymer "SAP") in place. - Structural adhesive: For bonding polyethylene backsheets to nonwoven fabric substrates, or for bonding two nonwoven fabric substrates. - Elastic adhesives: Used to bond elastic strands to polyethylene ("PE") (or polypropylene ("PP") and nonwoven fabric substrates.
[0005] Styrene-based block copolymer adhesives are the primary hot-melt adhesives used in the absorbent materials industry (core, elastic, and structural applications). Over the years, polyolefin-based adhesives have been incorporated thanks to the development of new polyolefin copolymers (Ziegler-Natta's Amorphous Poly-Alpha-Olefin "APAO" catalyst and subsequent metallocene catalysts).
[0006] In the disposable hygiene market, robustness of performance and processability, as well as low odor levels, are increasingly demanded. Currently, cohesiveness, adhesion, and processability are three properties that exhibit antagonistic interactions. Therefore, obtaining a hot-melt adhesive composition that shows a good compromise between these properties is difficult.
[0007] Hot-melt structural adhesives are used for permanent structures (or assemblies) by bonding various substrates through a lamination process. The materials used are selected from a variety of nonwoven materials such as polylactic acid, polyethylene, or polypropylene, or from low-surface-energy thermoplastic resin films. An example of such a permanent assembly in the case of diapers is the lamination of polyethylene (PE) sheets with polypropylene (PP) nonwoven fabric, the latter providing a silky appearance that is pleasing to the eye and touch.
[0008] The required level of cohesion for such permanent assemblies (or laminates) is typically quantified by a "peel" test.
[0009] Hot-melt structural adhesives are preferably designed to provide strong peel strength, especially at low coating weights such as 1-4 grams / square meter.
[0010] Typically, current polyolefin-based hot-melt adhesive compositions do not provide laminates with good retention of cohesive performance after aging at temperatures above 50°C. However, there is a need for a hot-melt adhesive composition that has stable cohesive performance both initially and over time at high temperatures. In fact, disposable nonwoven sanitary products such as diapers are sold worldwide, even in countries where temperatures are routinely high (e.g., above 40°C). Disposable nonwoven sanitary products are also exposed to high temperatures during transport and / or storage in these countries. [Overview of the project]
[0011] Therefore, there is a need for new and improved hot-melt adhesive compositions that are suitable as structural adhesives for disposable nonwoven sanitary products.
[0012] In particular, there is a need for a new hot-melt adhesive composition that provides a laminate with appropriate initial peel strength at a low coating weight in the range of 1 to 4 grams / square meter.
[0013] There is a need for a new hot-melt adhesive composition that provides laminates with appropriate initial peel strength and good peel strength over time for at least three weeks at high temperatures, such as above 50°C.
[0014] There is a further need for new hot-melt adhesive compositions that provide laminates with a good compromise between good adhesion and good peel strength over time, for at least three weeks at high temperatures, such as above 50°C. [Modes for carrying out the invention]
[0015] The present invention has a crystallization enthalpy of less than 5 J / g, a) A composition a) comprising at least 60% by weight, - At least one copolymer A having needle penetration of more than 15 dmm; - At least (co)polymer B with needle penetration of less than 15 dmm Composition a) comprising; b) 0 wt% to 30 wt% of at least one tackifying resin Relates to a hot melt adhesive composition comprising.
[0016] The contents of the above components a) and b) in the hot melt adhesive composition according to the present invention are represented in weight percent and are relative to the total weight of the hot melt adhesive composition according to the present invention.
[0017] A. Hot melt adhesive composition Composition a) As used herein, the term "(co)-polymer" encompasses both homopolymers and copolymers.
[0018] As used herein, the term "copolymer" refers to a polymer formed by the polymerization of at least two different monomers. The term "copolymer" can include terpolymers containing three different monomers.
[0019] Composition a) may have a viscosity in the range of 1000 mPa·s to 30000 mPa·s, preferably 4000 mPa·s to 20000 mPa·s, more preferably 5000 mPa·s to 15000 mPa·s at 149 °C.
[0020] The viscosity is the Brookfield viscosity measured at 149 °C according to ASTM D3236.
[0021] Preferably, composition a) contains at least 30 wt% of copolymer A, preferably at least 35 wt%, even more preferably at least 40 wt% of copolymer A based on the total weight of the above composition a).
[0022] Composition a) may contain 30 wt% to 90 wt% of copolymer A, preferably 35 wt% to 80 wt%, even more preferably 40 wt% to 70 wt% of copolymer A based on the total weight of the above composition a).
[0023] Preferably, composition a) comprises at least 20% by weight of (co)polymer B, preferably at least 25% by weight, and more preferably at least 30% by weight of copolymer B, based on the total weight of composition a).
[0024] Composition a) may contain 20% to 80% by weight of (co)polymer B, preferably 25% to 70% by weight, and more preferably 30% to 60% by weight of (co)polymer B, based on the total weight of composition a).
[0025] Composition a) may have a crystallization enthalpy in the range of 0 J / g to less than 5 J / g, more preferably 1.0 J / g to 4.5 J / g, and even more preferably 1.5 to 4.5 J / g.
[0026] According to the present invention, the crystallization enthalpy is determined by DSC analysis. Specifically, a 10 mg sample is cooled from 23°C to -70°C for 5 minutes under a nitrogen stream using a Mettler DSC analyzer. The heating rate is then adjusted to 10°C / min from -70°C to 200°C. After reaching 200°C, the cooling rate of the sample is adjusted to -10°C / min until it reaches -70°C.
[0027] In one embodiment, composition a) consists essentially of, preferably, the following: - At least one copolymer A having needle penetration of more than 15 dmm and preferably a crystallization enthalpy of less than 5 J / g; - At least (co)polymer B having a needle penetration of less than 15 dmm and preferably a crystallization enthalpy of less than 5 J / g.
[0028] In a preferred embodiment, composition a) is - One copolymer A having a needle penetration of more than 15 dmm and a crystallization enthalpy of less than 5 J / g; - One copolymer B having a needle penetration of less than 15 dmm and a crystallization enthalpy of less than 5 J / g Includes.
[0029] The hot melt adhesive composition may contain 60% to 99% by weight, preferably 60% to 95% by weight, more preferably 60% to 90% by weight, and even more preferably 70% to 90% by weight of composition a) as defined herein, based on the total weight of the hot melt adhesive composition.
[0030] Copolymer A Copolymer A may contain 30% to 80% by weight, preferably 40% to 80% by weight, of 1-butene monomer units.
[0031] Preferably, copolymer A contains more than 50% by weight of 1-butene monomer units.
[0032] Copolymer A is composed of one or more C 2-20 It may contain α-olefin monomer units.
[0033] In a preferred embodiment, copolymer A contains 30% to 70% by weight of C 2-20 Contains α-olefin monomer units.
[0034] C 2-20 The α-olefin monomer units can be selected from the group consisting of ethylene, propylene, pentene, dodecene-1, hexadodecene-1, decene-1, nonene-1, heptane-1, hexane-1, propene, dimethylpentene-1, methylnonene-1, trimethylheptene-1, 4-methyl-1-pentene, dimethylpentene-1, ethylpentene-1, methylpentene-1, trimethylpentene-1, and mixtures thereof.
[0035] Preferably, C 2-20 The α-olefin monomer unit is selected from the group consisting of propylene units, ethylene units, and mixtures thereof.
[0036] In a preferred embodiment, copolymer A is composed of 30% to 70% by weight of C selected from the group consisting of ethylene, propylene, and mixtures thereof. 2-20 Contains α-olefin monomer units.
[0037] The proportion of monomer units can be determined by appropriate methods known to those skilled in the art, such as nuclear magnetic resonance.
[0038] Preferably, copolymer A has a crystallization enthalpy of less than 5 J / g, preferably in the range of 1 to 5 J / g, more preferably in the range of 2 to 5 J / g, and even more preferably in the range of 2 to 4 J / g.
[0039] In a preferred embodiment, copolymer A has a crystallization enthalpy of less than 4 J / g.
[0040] The weight-average molecular weight of copolymer A may be in the range of 10,000 g / mol to 100,000 g / mol, preferably 20,000 g / mol to 75,000 g / mol.
[0041] The weight-average molecular weight is characterized using high-temperature size exclusion chromatography (SEC) with a polystyrene reference standard.
[0042] Copolymer A has needle penetration of more than 15 dmm, preferably more than 17 dmm, and more preferably more than 18 dmm.
[0043] In one embodiment, copolymer A has a needle penetration of less than 30 dmm, preferably less than 25 dmm.
[0044] According to the present invention, needle penetration is measured according to DIN EN 1426 with some modifications (heating the copolymer to 180°C in a thin can). After 24 hours (the time required for recrystallization of the amorphous copolymer), the hardness of the copolymer is determined using a needle at 25°C with a weight of 100g and a penetration time of 5 seconds into the sample.
[0045] As used herein, the term "dmm" means decimeter.
[0046] Copolymer A has a density of approximately 0.80 g / cm³ at 23°C, as measured according to ASTM D1505.3 ~about 0.90 g / cm 3 、preferably about 0.85 g / cm 3 ~about 0.88 g / cm 3 and can be.
[0047] As an example of copolymer A, Vestoplast® EP 2094 commercially available from Evonik is a butene-rich copolymer having a viscosity of 2500 MPa·s at 190 °C, a needle penetration of 20 dmm, and a crystallization enthalpy of 3.7 J / g. Other examples are Eastoflex® E1045 PL from EASTMAN, Eastoflex® E1003, or Vestoplast® 751 from EVONIK.
[0048] (Co)polymer B (Co)polymer B may be a homopolymer or a copolymer. Preferably, (co)polymer B is a copolymer.
[0049] (Co)polymer B may contain 30 wt% to 80 wt%, preferably 40 wt% to 80 wt% of 1-butene monomer units.
[0050] Preferably, (co)polymer B contains more than 50 wt% of 1-butene monomer units.
[0051] (Co)polymer B may contain one or more C 2-20 α-olefin monomer units.
[0052] In a preferred embodiment, (co)polymer B contains 30 wt% to 70 wt% of C 2-20 α-olefin monomer units.
[0053] C 2-20The α-olefin monomer units can be selected from the group consisting of ethylene, propylene, pentene, dodecene-1, hexadodecene-1, decene-1, nonene-1, heptane-1, hexane-1, propene, dimethylpentene-1, methylnonene-1, trimethylheptene-1, 4-methyl-1-pentene, dimethylpentene-1, ethylpentene-1, methylpentene-1, trimethylpentene-1, and mixtures thereof.
[0054] Preferably, C 2-20 The α-olefin monomer unit is selected from the group consisting of propylene units, ethylene units, and mixtures thereof.
[0055] In a preferred embodiment, (co)polymer B is 30% to 70% by weight of C selected from the group consisting of ethylene, propylene and mixtures thereof. 2-20 Contains α-olefin monomer units.
[0056] The proportion of monomer units can be determined by appropriate methods known to those skilled in the art, such as nuclear magnetic resonance.
[0057] Preferably, the (co)polymer B has a crystallization enthalpy of less than 5 J / g, preferably in the range of 1 to 5 J / g, more preferably in the range of 2 to 5 J / g, and even more preferably in the range of 2 to 4 J / g.
[0058] In a preferred embodiment, the (co)polymer B has a crystallization enthalpy of less than 4 J / g.
[0059] The weight-average molecular weight of (co)polymer B may be in the range of 10,000 to 100,000 g / mol, preferably 20,000 to 75,000 g / mol.
[0060] Copolymer B has a needle penetration of less than 15 dmm. Preferably, copolymer B has a needle penetration of more than 5 dmm, more preferably more than 8 dmm, and especially more than 10 dmm.
[0061] Copolymer B has a density of approximately 0.85 g / cm³ at 23°C, as measured according to ASTM D1505. 3 ~Approx. 0.90g / cm 3 Preferably about 0.86 g / cm³ 3 ~Approx. 0.88g / cm 3 It is possible.
[0062] As an example of (co)polymer B, Vestoplast® 508, commercially available from Evonik, is a butene-rich copolymer with a viscosity of 8000 MPa.s at 190°C, a needle penetration of 14 dmm, and a crystallization enthalpy of 3.7 J / g. Other examples include Vestoplast® 703 or Vestoplast® EP V2103 from EVONIK.
[0063] Adhesion-imparting resin The hot melt adhesive composition of the present invention contains at least one tackifying resin in an amount of 0% to 30% by weight.
[0064] Preferably, the content of the tackifying resin is in the range of 1% to 30% by weight, preferably 5% to 30% by weight, and more preferably 10% to 30% by weight, based on the total weight of the hot melt adhesive composition.
[0065] The above-mentioned tackifying resin may contain one or more carbon-carbon double bonds, or it may not contain any carbon-carbon double bonds. In the latter case, a saturated tackifying resin can be prepared by the total hydrogenation of an unsaturated tackifying resin.
[0066] The tackifying resin is preferably selected from the following classes. (a) Natural and modified rosins, such as gum rosin, wood rosin, tall oil rosin, distilled rosin, hydrogenated rosin, dimerized rosin and polymerized rosin; (b) Glycerol and pentaerythritol esters of natural and modified rosins, e.g., glycerol ester of wood rosin, glycerol ester of hydrogenated rosin, glycerol ester of polymerized rosin, pentaerythritol ester of wood rosin, pentaerythritol ester of hydrogenated rosin, pentaerythritol ester of tall oil rosin, and phenol-modified pentaerythritol ester of rosin; (c) Polyterpene resins include hydrogenated polyterpene resins having a ring-spherical softening point of about 20°C to 140°C, the latter of which are typically obtained from the polymerization of terpene hydrocarbons, such as monoterpenes known as pinene, in the presence of a Friedel-Crafts catalyst at moderately low temperatures; (d) Phenol-modified terpene resins, such as those resulting from the condensation of terpenes and phenols in an acidic medium; (e) Aliphatic (including alicyclic) petroleum hydrocarbon resins (C5) having a ring-spherical softening point of approximately 60°C to 140°C, which are resins resulting from the polymerization of C5 hydrocarbon monomers; and corresponding hydrogenated derivatives resulting from their subsequent total or partial hydrogenation; (f) Aromatic petroleum hydrocarbon resins (C9) having a ring-spherical softening point of approximately 60°C to 140°C, which are resins obtained from the polymerization of C9 hydrocarbon monomers; and corresponding hydrogenated derivatives obtained from the subsequent total or partial hydrogenation thereof; (g) Aliphatic (including alicyclic) and / or aromatic petroleum resins (C5 / C9) having a ring-spheroid softening point of approximately 60°C to 140°C, which are resins resulting from the polymerization of C5 / C9 hydrocarbon monomers; and corresponding hydrogenated derivatives resulting from the subsequent total or partial hydrogenation thereof.
[0067] Examples of C5 hydrocarbon monomers useful for preparing tackifying resins belonging to class (e) or (g) include trans-1,3-pentadiene, cis-1,3-pentadiene, 2-methyl-2-butene, dicyclopentadiene, cyclopentadiene, cyclopentene, and any mixture thereof.
[0068] Examples of C9 hydrocarbon monomers useful for preparing tackifying resins belonging to class (f) or (g) include vinyltoluene, dicyclopentadiene, indene, methylstyrene, styrene, methylindene, and any mixture thereof.
[0069] Examples of commercially available tackifying resins belonging to class (a) include the following: - Unmodified natural tall oil rosin from Kraton Company, sold under the trade names SYLVAROS® (85, 90 and NCY), - Partially hydrogenated rosin from EASTMAN Company sold under the brand name FORALYN(registered trademark)E, and fully hydrogenated rosin from Eastman sold under the brand name FORAL(registered trademark)AX-E. - Dimerized rosin from EASTMAN Company, sold under the product name DYMEREX (registered trademark). Examples of commercially available tackifying resins belonging to class (b) include the following: - SYLVALITE® RE 100L, a pentaerythritol-based tall oil rosin ester, and - SYLVALITE(registered trademark) RE 85L, a glycerol ester of tall oil rosin. Both are available from Kraton Company.
[0070] Examples of commercially available tackifying resins belonging to class (c) include the following: - Polyterpene tackifiers from KRATON Company, sold under the product names SYLVAGUM®TR and SYLVARES®TR series (7115, 7125, A25L, B115, M1115).
[0071] Examples of commercially available tackifying resins belonging to class (d) include the following: - Terpene phenol resin from KRATON Company, sold under the trade name SYLVARES(registered trademark)TP(96, 2040, 300, 7042, 2019).
[0072] Examples of commercially available tackifying resins belonging to class (e) include the following: - Aliphatic and alicyclic petroleum hydrocarbon resins based on C5 petroleum hydrocarbon fractions (e.g., mixtures of trans-1,3-pentadiene, cis-1,3-pentadiene, 2-methyl-2-butene, dicyclopentadiene, cyclopentadiene, and cyclopentene) having ring-spherical softening points in the range of 60°C to 140°C, from EASTMAN Company under the trade names WINGTACK® 98 and WINGTACK® ET, and from EXXONMOBIL under the trade name ESCOREZ® 1310LC. - Partially aliphatic and alicyclic petroleum hydrocarbon resins from KOLON Company, sold under the trade names SUKOREZ® SU210 and SUKOREZ® 230, based on C5 petroleum hydrocarbon fractions (e.g., mixtures of trans-1,3-pentadiene, cis-1,3-pentadiene, 2-methyl-2-butene, dicyclopentadiene, cyclopentadiene, and cyclopentene), having a cyclic softening point in the range of 80°C to 140°C. The softening point of SUKOREZ® SU210 is 110°C. - A fully hydrogenated alicyclic petroleum hydrocarbon resin based on the dicyclopentadiene-petroleum hydrocarbon fraction, sold under the product names ESCOREZ® 5400 series (5400, 5415, 5490), with a ring-spherical softening point in the range of 60°C to 140°C, from EXXONMOBIL. The softening point of ESCOREZ® 5400 is 100°C.
[0073] Examples of commercially available tackifying resins belonging to class (f) include the following: - Aromatic petroleum hydrocarbon resins based on C9 hydrocarbon petroleum fractions (e.g., mixtures of vinyltoluene, dicyclopentadiene, indene, methylstyrene, styrene, and methylindene), available from KOLON INDUSTRIES under the trade name HIKOTACK® (P-90, P110 S, and P120 S), having a ring-spherical softening point of approximately 60°C to 140°C.
[0074] Examples of commercially available tackifying resins belonging to class (g) include the following: - Partially hydrogenated alicyclic-modified aromatic petroleum hydrocarbon resins based on C5 / C9 hydrocarbon petroleum fractions, sold under the product names ESCOREZ® 5600 series (5600, 5615, 5690) by EXXONMOBIL Company, with a ring-spherical softening point of approximately 60°C to 140°C. The softening point of ESCOREZ® 5600 is 100°C. - A non-hydrogenated aliphatic-modified aromatic hydrocarbon petroleum resin based on C5 / C9 hydrocarbon petroleum fractions, sold by ZEON under the trade name QUINTONE® DX390N, with a softening point of 93°C.
[0075] According to a preferred embodiment, the ring-shaped (or softening point) of the tackifying resin is preferably in the range of 90°C to 125°C, and more preferably in the range of 90°C to 115°C.
[0076] The softening temperature (or point) is determined according to the standardized ASTM E 28 test, the principle of which is as follows: A brass ring with a diameter of approximately 2 cm is filled with the molten resin of the test. After cooling to room temperature, the ring and solid resin are placed horizontally in a thermostat-controlled glycerol bath in which the temperature can change by 5°C per minute. A steel ball with a diameter of approximately 9.5 mm is placed in the center of the solid resin disc. The softening temperature is the temperature at which the resin disc flows by a volume of 25.4 mm under the weight of the ball while the bath temperature is increased at a rate of 5°C / min.
[0077] plasticizer The hot melt adhesive composition may contain a plasticizer.
[0078] Any plasticizer known to those skilled in the art can be used.
[0079] Non-limiting examples of plasticizers include olefin oligomers, low molecular weight polyolefins such as liquid polybutene, low molecular weight non-aromatic polymers, phthalates, mineral oils such as naphthenic oil, paraffin oil, waxes, vegetable oils and animal oils, and their derivatives.
[0080] Examples of plasticizers include polyethylene, polypropylene, polybutene, polyisobutylene, hydrogenated polyisoprene, and hydrogenated polybutadiene, with average molecular weights ranging from approximately 350 g / mol to 10,000 g / mol. Suitable vegetable and animal oils include glycerol esters of common fatty acids and their polymerization products.
[0081] Wax can be used to reduce the melt viscosity of hot-melt adhesive compositions. Examples of waxes include: 1. Low molecular weight polyethylene, i.e., with a number-average molecular weight (Mn) equal to 500-6000 g / mol, a hardness value of approximately 0.1-120 as determined by ASTM method D-1321, and an ASTM softening point of approximately 65°C-140°C; 2. Petroleum waxes such as paraffin wax with a melting point of approximately 50°C to 80°C and microcrystalline wax with a melting point of approximately 55°C to 100°C; the melting point of the latter is determined by ASTM method D 127-60; 3. Synthetic waxes produced by polymerizing carbon monoxide and hydrogen, for example, Fischer-Tropschwax; Furthermore 4. Polyolefin waxes. As used herein, the term “polyolefin waxes” refers to polymerizable or long-chain entities composed of olefinic monomer units. This type of material is commercially available from Westlake Chemical Corporation (Houston, Texas) under the trade name “Epolene” and from Honeywell Corporation (Morristown, New Jersey) under the trade name “AC”.
[0082] In preferred embodiments, the hot-melt adhesive composition is polyisobutylene-free and, more preferably, plasticizer-free.
[0083] Optional ingredients Antioxidants Preferably, the hot melt adhesive composition according to the present invention contains at least one antioxidant in an amount of 0.1% to 2% by weight relative to the total weight of the hot melt adhesive composition.
[0084] Antioxidants useful in the present invention are preferably incorporated into the hot melt adhesive composition to help protect the hot melt adhesive composition from chemical decomposition. This decomposition generally involves the reaction of free radicals with dioxygen resulting from chain breakage catalyzed by either ultraviolet light or heat. Such decomposition usually manifests as deterioration of the appearance (browning of color) or other physical properties of the adhesive, and the performance properties of the adhesive.
[0085] In particular, antioxidants protect the hot-melt adhesive composition and its components from the effects of thermal decomposition reactions that primarily occur during the manufacturing and application processes of the adhesive, where the adhesive is heated at high temperatures for extended periods in the presence of two oxygen atoms.
[0086] Useful antioxidants include hindered phenols and sulfur and phosphorus-containing phenols. Hindered phenols are well known to those skilled in the art and can be characterized as phenol compounds that also contain sterically bulky groups adjacent to their phenolic hydroxyl groups. In particular, tertiary butyl groups are generally substituted on the benzene ring at least one ortho position relative to the phenolic hydroxyl group.
[0087] Typical hindered phenols include the following: 1,3,5-Trimethi-1-2,4,6-Tris(3-5-di-tert-butyl-4-hydroxybenzyl)benzene; Pentaerythritol tetrakis-3(3,5-di-tert-buty-1-4-hydroxyphenyl)propionate; n-octadecyl-3(3,5-ditert-butyl-4-hydroxyphenyl)propionate; 4,4'-Methylenebis(4-methyl-6-tert-butylphenol); 4,4'-thiobis(6-tert-butyl-o-cresol); 2,6-di-tert-butylphenol; 6-(4-hydroxyphenoxy)-2,4-bis(n-octylthio)-1,3,5-triazine; 2,4,6-tris(4-hydroxy-3,5-di-tert-butyl-phenoxy)-1,3,5-triazine; di-n-octadecyl-3,5-di-tert-butyl-4-hydroxybenzylphosphonate; 2-(n-octylthio)ethyl-3,5-di-tert-butyl-4-hydroxybenzoate; Sorbitol hexa-(3,3,5-di-tert-butyl-4-hydroxyphenyl)propionate; 2,2'-Methylenebis(4-methyl-6-tert-butylphenol) phosphites, e.g., tris-(p-nonylphenyl)-phosphite (TNPP) and bis(2,4-di-tert-butylphenyl)4,4'-diphenylene-diphosphonite, di-stearyl-3,3'-thiodipropionate (DSTDP); Tetrakis(methylene(3,5-di-ter-butyl-4-hydroxyhydrocinnamate))methane; (Tris(2,4-ditert-butylphenyl) phosphate), and combinations thereof.
[0088] Hindered phenol antioxidants can be used alone or in combination with other antioxidants, such as phosphite antioxidants like the IRGAFOS® series or aromatic amine antioxidants like the NAUGARD® series from ADDIVANT.
[0089] Useful antioxidants are commercially available under various brand names, such as the hindered phenol antioxidants in BASF's IRGANOX® series, including IRGANOX® 1010 (tetrakis(methylene(3,5-di-ter-butyl-4-hydroxyhydrocinnamate))methane) and IRGAFOS® 168 antioxidant (tris(2,4-ditert-butylphenyl)phosphate).
[0090] The total amount of antioxidant is preferably in the range of 0.1 to 3% by weight, more preferably 0.4% to 1% by weight, relative to the total weight of the hot melt adhesive composition.
[0091] Other ingredients Other optional components may be incorporated into the hot-melt adhesive composition according to the present invention to modify some of its physical properties.
[0092] Among the optional components, examples include fillers, surfactants, colorants, UV stabilizers, fluorescent agents, and rheological modifiers.
[0093] The total amount of these optional components may be in the range of 0% to 10% by weight, preferably 0.1% to 5% by weight, and more preferably 0.1% to 2% by weight, relative to the total weight of the hot melt adhesive composition.
[0094] Hot melt adhesive composition According to a preferred embodiment, the hot-melt adhesive composition according to the present invention has a Brookfield viscosity in the range of 1,000 mPa.s to 30,000 mPa.s, preferably 2,000 to 20,000, and more preferably 4,000 to 15,000 mPa.s, measured at 149°C. The Brookfield viscosity is measured according to ASTM D-3236 using a Brookfield thermocell viscometer.
[0095] The hot melt adhesive composition may contain 35% to 70% by weight of copolymer A, preferably 40% to 70% by weight of copolymer A, and more preferably 40% to 60% by weight of copolymer A, based on the total weight of the hot melt adhesive composition.
[0096] The hot melt adhesive composition may contain 30% to 70% by weight of (co)polymer B, preferably 30% to 60% by weight of (co)polymer B, and more preferably 30% to 50% by weight of (co)polymer B, based on the total weight of the hot melt adhesive composition.
[0097] In the hot-melt adhesive composition of the present invention, the weight ratio of copolymer A to (co)polymer B may be in the range of 30:70 to 80:20, preferably 50:50 to 75:25.
[0098] The hot melt adhesive composition has a crystallization enthalpy of less than 5 J / g. Preferably, the hot melt adhesive composition has a crystallization enthalpy in the range of 0.5 J / g to less than 5 J / g, and more preferably in the range of 1.5 J / g to 4.5 J / g.
[0099] In one embodiment, the hot melt adhesive composition of the present invention has a crystallization enthalpy of less than 5 J / g. a) A composition a) comprising at least 60% by weight, - At least one copolymer A having needle penetration of more than 15 dmm; - At least (co)polymer B with needle penetration of less than 15 dmm; Composition a) containing b) At least one tackifying resin in an amount of 0% to 30% by weight; Includes, The copolymer A above contains one or more C 2-20 Contains α-olefin monomer units, The above (co)polymer B contains one or more C 2-20 Contains α-olefin monomer units.
[0100] In one preferred embodiment, the hot melt adhesive composition of the present invention is - a) A composition a) comprising 70% to 99% by weight, - Copolymer A having needle penetration of more than 15 dmm and preferably a crystallization enthalpy of less than 5 J / g; - Copolymer B having a needle penetration of less than 15 dmm and preferably a crystallization enthalpy of less than 5 J / g; Includes, Composition a, in which both copolymer A and copolymer B contain more than 50% by weight of 1-butene monomer units); - b) At least one tackifying resin in an amount of 3% to 30% by weight. Includes.
[0101] The hot-melt adhesive composition of the present invention can be manufactured using any of the techniques known in the art. The components used are preferably mixed and heated at a high temperature for at least several hours, typically at least 4 hours, preferably 4 to 6 hours, at a temperature in the range of 140°C to 170°C.
[0102] The hot-melt adhesive composition according to the present invention can be prepared in the presence of two oxygen atoms (such as in an air atmosphere), or preferably in an inert atmosphere, such as carbon dioxide or nitrogen, in order to limit potential decomposition due to oxidation reactions.
[0103] According to a preferred embodiment, a method for producing a hot-melt adhesive composition according to the present invention is: - A first step of mixing copolymer A, an optional tackifying resin, and preferably an antioxidant if present, at a temperature in the range of 140°C to 180°C for a sufficiently long time to obtain at least a homogeneous mixture; - A second step in which (co)polymer B is added to the mixture obtained in the previous step, while stirring and heating at a temperature in the range of 140°C to 180°C for a sufficiently long time to obtain at least a homogeneous mixture. Includes.
[0104] Furthermore, the method of the present invention may include a step of applying a vacuum to remove trapped air from the mixture before or after any of the steps of the method described above.
[0105] Other useful optional components that may be present in the hot-melt adhesive composition according to the present invention may be added at any step of the method according to the present invention.
[0106] The hot-melt adhesive composition according to the present invention, prepared by the method described above, may be kept in a molten state for up to 15 hours in a melting vessel, for example, and then cooled and packaged in the form of a ready-to-use solid composition.
[0107] B. Use The present invention relates to the use of the hot-melt adhesive compositions described herein in sanitary disposable consumer articles, such as diapers, feminine hygiene pads, and sanitary napkins. The articles may include articles having any two or more substrates bonded together by the hot-melt adhesive composition, such as disposable articles like diapers or feminine napkins.
[0108] The substrate may include thermoplastic resins, thermosetting polymers, polyesters, polyethylene terephthalate, polyamides, nylons, polypropylenes, and combinations, blends, or layered composite materials thereof. In some applications, the substrate may include coatings of waxes, acrylate polymers, or other materials, colorants, preservatives, stabilizers, processing lubricants, and combinations thereof. The substrate may include solid, non-porous, or breathable films. In some applications, the substrate may include nonwoven fabrics and films (e.g., polyethylene films).
[0109] Hot-melt adhesive compositions can be used as structural adhesives in the assembly of commonly available consumer waste products. Such articles include infant diapers, adult diapers, bed pads, hygiene products, and other absorbent articles. These articles are typically made by combining at least a polymer film with other films and fibrous materials. Fibrous materials may include fabrics such as woven or nonwoven fabrics, fibers in the form of fiber vats, fiber collections, fiber balls, and the like.
[0110] Such absorbent articles typically contain an absorbent material held within the article. The absorbent material is usually covered with a nonwoven inner liner. Such liners contain highly permeable materials, such as spunbond nonwoven fabric structures, that allow fluids or moisture to pass from the inside of the article to the absorbent layer. The absorbent layer or structure formed within the absorbent article typically contains a fibrous pad or cellulose or wood pulp for the purpose of absorbing liquids or fluid materials released into the absorbent article. The fibers or fluff may include cellulose fibers, synthetic fibers or mixtures thereof, such as wood fibers, cellulose fibers, polyethylene fibers, polypropene fibers, or blends of other fibrous materials, often including superabsorbent materials. Superabsorbent or highly absorbent materials are used to enhance the absorbency of the absorbent article. Such materials are organic materials, including modified natural gums and resins, but often include synthetic polymer materials such as hydrogels. Carboxymethylcellulose, alkali metal salts of acrylic polymers, polyacrylamide, polyvinyl alcohol, polyethylene anhydride polymers and copolymers, polyvinyl ether polymers and copolymers, hydroxyalkylcellulose polymers and copolymers, polyvinyl sulfonic acid polymers and copolymers, polyacrylic polymers, and polyvinylpyrrolidone polymers and copolymers can be used for absorption functions.
[0111] Nonwoven fabric layers used in such waste materials are typically nearly planar structures containing bonded assemblies of natural or synthetic fibers.
[0112] Such nonwoven materials are often manufactured using a variety of techniques, including spunbonding and hot bonding. These nonwoven materials are often produced by randomly arranging fibers or rovings in a random pattern, and then bonding the fibers using the inherent bonding properties of the fibers, or using a resin material coated on the fibers. Various polymers can be used to produce nonwoven materials, including polyolefins, polyesters, ethylene vinyl acetate polymers, and ethylene acrylic acid polymers.
[0113] The outer covering of an article often includes a liquid-impermeable polymer film. In certain embodiments, the outer polymer film may be further modified by using an additional outer layer to obtain more fabric-like or nonwoven properties relative to the outer polymer film. The outer film typically includes a single layer polymer film, but may also be a multilayer film structure. Typical polymer sheet materials include high-tensile strength polymers, including polyester, polyolefin, or other thermoplastic resin sheet materials that can be formed into film layers. Polyolefin or polyester polymer materials are often formed into sheets and treated to improve strength, flexibility, and puncture resistance. Techniques including biaxial orientation, heat treatment, or surface treatment can improve the film properties of the polymer film. Such polymer films often have thicknesses ranging from about 0.5 mil (e.g., 1 / 1000 inch) to about 1.5 mil.
[0114] The absorbent article may include a liquid-impermeable polymer film, an absorbent layer pad, and a nonwoven inner layer. The three-component structure can be assembled using an adhesive composition applied using a manufacturing technique that adheres the nonwoven inner layer to the polymer film while holding the absorbent layer in between.
[0115] This application relates to a method for manufacturing an assembled product (or laminate), - (i) Heating the hot melt adhesive composition according to the present invention at a temperature in the range of 130°C to 180°C for a sufficiently long time (e.g., at least 2 hours on an industrial scale) to make the hot melt adhesive composition liquid enough to be applied to a substrate, then - (ii) A step of coating the above composition onto a primary substrate, then - (iii) A step of bringing the coated surface of the primary substrate into contact with the surface of the secondary substrate to form an adhesive joint that connects the two substrates. Regarding methods including
[0116] The substrate may have different or the same properties in various forms (layers or films, strands, fluff).
[0117] Preferably, each substrate can be independently selected from nonwoven fabrics, tissues, absorbent lint, superabsorbent polymers (SAPs), composite materials, plastics which may be elastomers or non-elastomers and may be selected from, for example, styrene block copolymers (SBCs), polyurethanes and polyolefins, and any mixture thereof. A composite material may consist of at least one of the materials described above. Nonwoven fabrics are defined as interlocking fiber networks characterized by flexibility, porosity and integrity. The individual fibers used to constitute the nonwoven fabric may be synthetic fibers, natural fibers, or a combination of the two. The individual fibers may be bonded to each other mechanically, chemically or thermally.
[0118] The hot melt adhesive composition according to the present invention can be coated or applied using a variety of coating techniques known in the art, including contact coating (such as slot die coating) and non-contact coating (such as spraying, fiberization, or comb slot coating).
[0119] In particular, as described above, the hot melt adhesive composition according to the present invention can be easily applied through conventional coating nozzles, such as those having a diameter of 0.305 to 0.762 mm, or a slot die length in the range of 20 μm to 300 μm, which can be adjusted by shims.
[0120] The amount of adhesive coated on a surface-by-surface basis varies from 0.1 to 50 g / m², depending on the substrate to be bonded. 2 It can vary over a very wide range. For example, in the case of a nonwoven fabric substrate bonded with polyethylene film to manufacture a cloth-like backsheet assembly, it can range from 0.2 to 1 g / m². 2 The range can be given as follows: for disposable multilayer assemblies, 3-7 g / m². 2 A range of 20-40 g / m² can be used. For example, when high shear performance is required, such as when attaching elastic side panels or fastening tapes to a diaper chassis, 20-40 g / m² is used. 2A much wider range can also be used.
[0121] Before being applied to the surface of a primary substrate, the hot-melt adhesive composition according to the present invention may be held in a melting vessel for up to four days.
[0122] The hot-melt adhesive composition according to the present invention can be applied to a substrate or stored in the presence of oxygen (in an air atmosphere), or preferably in an inert atmosphere, in order to limit decomposition by oxidation.
[0123] In another aspect, the application also relates to an assembled product comprising at least two substrates bonded together by at least one hot-melt adhesive composition according to the present invention.
[0124] The bonded substrate may be selected from the substrates listed above for the process of applying the hot melt adhesive composition according to the present invention.
[0125] The hot-melt adhesive composition according to the present invention can be used as a laminating adhesive for bonding multiple substrate layers to manufacture absorbent articles such as toilet tissues, paper towels, wipes and other consumer products, particularly disposable hygiene products, and more specifically, disposable diapers.
[0126] In certain embodiments of the present invention, the assembled product according to the present invention may be a multilayer product comprising at least two substrates bonded together by at least one hot-melt adhesive composition according to the present invention.
[0127] In the assembled product according to the present invention, at least two layers of the substrate may be bonded together by a layer of the hot-melt adhesive composition according to the present invention sandwiched between the two layers of the substrate.
[0128] Alternatively, or cumulatively, at least two layers of the substrate may be bonded together by spot bonding of the hot-melt adhesive composition according to the present invention.
[0129] Preferably, the assembled product is a disposable nonwoven absorbent article.
[0130] The hot melt composition according to the present invention advantageously provides a laminate having appropriate initial peel strength and good peel strength over time for at least three weeks at high temperatures, for example, above 50°C.
[0131] The hot-melt adhesive composition advantageously provides a laminate that has a good compromise between good adhesion and good peel strength over time, for at least three weeks at high temperatures, for example, above 50°C.
[0132] According to the present invention, "includes x~y" or "lies within the range of x~y" means a range that includes boundary values x and y. For example, the range "includes 1%~3%" specifically includes 1% and 3%.
[0133] The following embodiments are given purely as examples of the present invention and should not be construed under any circumstances as limiting its scope. [Examples]
[0134] Experimental section Test method The crystallization enthalpy is determined by DSC analysis. Using a Mettler DSC analyzer, a 10 mg sample is cooled from 23°C to -70°C for 5 minutes under a nitrogen stream. The heating rate is then adjusted to 10°C / min from -70°C to 200°C. After reaching 200°C, the cooling rate of the sample is adjusted to -10°C / min until it reaches -70°C.
[0135] Needle penetration is measured according to DIN EN 1426 with some modifications (heating the copolymer to 180°C in a thin can). After 24 hours (the time required for recrystallization of the amorphous copolymer), the hardness of the copolymer is determined using a needle with a weight of 100g at 25°C, with a penetration time of 5 seconds.
[0136] The following components were used in the preparation of the hot melt adhesive composition. - VESTOPLAST® EP V2094 (commercially available from EVONIK): A 1-butene-rich α-olefin copolymer with a low viscosity of 2500 MPa.s at 190°C, needle penetration of 20 dmm, and crystallization enthalpy of 3.7 J / g; - VESTOPLAST® 508 (commercially available from EVONIK): A 1-butene-rich α-olefin copolymer with a viscosity of 8000 MPa.s at 190°C, needle penetration of 14 dmm, and crystallization enthalpy of 3.7 J / g; - AERAFIN® 17 (commercially available from Eastman): A polyethylene / polypropylene copolymer with a low viscosity of 1700 MPa.s at 190°C, needle penetration of 20 dmm, and crystallization enthalpy of 24 J / g; - VISTAMAXX(registered trademark) 8880 (commercially available from EXXONMOBIL): Primarily composed of isotactic propylene repeating units with 6% by weight of ethylene, exhibiting a low viscosity of 1200 MPa.s at 190°C and a crystallization enthalpy of 34 J / g; - ESCOREZ® 5400 (commercially available from Exxonmobile): A fully hydrogenated alicyclic petroleum hydrocarbon resin based on the dicyclopentadiene-petroleum hydrocarbon fraction, having a ring-spherical softening point in the range of 103°C; - INDOPOL® H100 (commercially available from INEOS): A liquid polybutene oligomer having a viscosity of 200-235 mPa·s and a molecular weight of 910 g / mol at 100°C; - IRGANOX 1010: Phenolic primary antioxidant: Pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl))propionate
[0137] A1 - Preparation of hot melt adhesive composition The composition of Example 1 in Table 1 according to the present invention is prepared by a simple mixing of its components.
[0138] Mix the resin, copolymer A, and stabilizer together and heat at 160°C until all are dissolved as a homogeneous mixture. Then, add copolymer B at the same temperature until all are dissolved as a homogeneous mixture. Finally, cool and collect the mixture and use it as is.
[0139] The compositions of Example 1 in Table 1 from Comparative Examples D and E are prepared by simple mixing of their components. Copolymer A and the stabilizer are mixed together and heated at 160°C until all are dissolved as a homogeneous mixture. Copolymer B is then added at the same temperature until all are dissolved as a homogeneous mixture. Subsequently, INDOPOL H-300 is added to fluidize the mixture. Finally, the mixture is cooled and collected and used as is.
[0140] Preparation of laminate A2 using the A2-comb slot Signature™ coating apparatus: Laminate A2 is prepared as follows. As the lamination equipment, we will use a machine that operates continuously at a line speed of approximately 200 m / min, sold by Nordson under the name Coater CTL 4400.
[0141] In this machine, the coating nozzle is a Signature spray nozzle (NORDSON Comb Slot Signature® trademark).
[0142] The two base materials used are as follows: - A PE film with a width of 20 cm and a thickness of 13 μm, and - A spunmelt nonwoven fabric sheet of the same width and weight of 15 g / m2, composed of polypropylene (PP) fibers.
[0143] These two base materials are packaged as a reel with a width of 20 cm.
[0144] The composition of Example 1 is heated in a melting pot at a temperature of 155°C.
[0145] Next, this is coated onto the PE film at the same temperature of 155°C and with a coating weight of approximately 5 g / m2.
[0146] The resulting coating pattern is sufficiently suitable and typically exhibits good sprayability (and processability). This corresponds to a 2.54 cm wide discontinuous layer consisting of offset helical beads located in the center of the PE film and aligned along an axis perpendicular to the reel axis.
[0147] Next, the nonwoven (PP) sheet is brought into contact with the coated surface of the PE film using a nip roll that applies a pressure of 1 bar.
[0148] A3 - Delamination of laminate A2, measured initially and after aging at 23°C: Next, the resulting laminate A2 is packaged as a reel and left at room temperature and 50% relative humidity for 24 hours.
[0149] Next, a rectangular strip measuring approximately 25 mm x 10 cm is cut into the coated central region of the laminate.
[0150] Separate the two individual substrates from one end of the rectangular strip (used as a test specimen) by approximately 2 cm.
[0151] The two free ends obtained in this way are then fixed to two clamping devices, one connected to the fixed part and the other to the movable part of a tensile testing device located on the vertical axis.
[0152] The drive mechanism transmits a uniform speed of 300 mm / min to the movable part, resulting in the two substrates being gradually displaced and separated along the vertical axis, with their separated ends forming a 180° angle. The fixed part is connected to a dynamometer to measure the force with which the thus held test specimen can withstand.
[0153] The result corresponding to peeling after 24 hours at 23°C is expressed as N / 25mm.
[0154] Delamination after 4 weeks at 55°C was measured by repeating the above protocol, except that the assembled material obtained after lamination was aged at 55°C for the respective times, then measured at 23°C for 24 hours, and expressed as N / 25mm.
[0155] The results are reported in Table 2 below.
[0156] Example 1: Hot melt adhesive compositions A, B, C, D, and E The hot melt adhesive composition is prepared based on the components listed in Table 1 below. TIFF2023506847000001.tif72170
[0157] The components are mentioned as weight % of the total weight of the hot melt adhesive composition.
[0158] Example 2: Peeling performance Table 2 below shows the initial and post-aging delamination performance as described above. TIFF2023506847000002.tif36170
[0159] Table 2 clearly shows that the hot-melt adhesive compositions (A and B) according to the present invention result in laminates with improved cohesive properties after aging at 55°C for 4 weeks. In fact, delamination increases favorably from 1.71 to 2.15 (hot-melt A) and from 1.7 to 2.28 (hot-melt B).
[0160] In comparison, comparative hot melt adhesives C, D, and E show a high reduction in peeling after aging at 55°C for 4 weeks.
Claims
1. having a crystallization enthalpy of less than 5 J / g; a) at least 60% by weight of composition a), at least one copolymer A having a penetration of more than 15 dmm; - at least (co)polymer B with a needle penetration of less than 15 dmm; A composition comprising: b) greater than or equal to 0% and less than or equal to 30% by weight of at least one tackifying resin; A hot melt adhesive composition comprising: copolymer A comprises from 30% to 80% by weight of 1-butene monomer units, the (co)polymer B comprises from 30% to 80% by weight of 1-butene monomer units, Hot melt adhesive compositions.
2. 2. The hot melt adhesive composition according to claim 1, wherein the (co)polymer B has a crystallization enthalpy of less than 5 J / g.
3. 3. The hot melt adhesive composition according to claim 1, wherein Copolymer A has a crystallization enthalpy of less than 5 J / g.
4. The hot melt adhesive composition according to any one of claims 1 to 3, wherein Copolymer A contains 40% to 80% by weight of 1-butene monomer units.
5. 5. The hot melt adhesive composition according to claim 1, wherein the (co)polymer B comprises from 40% to 80% by weight of 1-butene monomer units.
6. - copolymer A contains one or more C 2-20 comprises α-olefin monomer units, and - (co)polymer B is one or more C 2-20 Contains α-olefin monomer units, The hot melt adhesive composition according to any one of claims 1 to 5.
7. - copolymer A is 30% to 70% by weight of C 2-20 and / or - (co)polymer B is 30% to 70% by weight of C 2-20 Contains α-olefin monomer units; The hot melt adhesive composition according to any one of claims 1 to 6.
8. The hot melt adhesive composition according to any one of claims 1 to 7, wherein Copolymer A has a penetration of less than 30 dmm.
9. 9. The hot melt adhesive composition according to claim 1, wherein the (co)polymer B has a penetration of more than 5 dmm.
10. Composition a) is - from 30% to 90% by weight of copolymer A, based on the total weight of said composition a); and / or from 20% to 80% by weight of (co)polymer B, based on the total weight of said composition a); The hot melt adhesive composition according to any one of claims 1 to 9, comprising:
11. 11. The hot melt adhesive composition according to any one of claims 1 to 10, comprising 60% to 99% by weight of composition a), based on the total weight of the hot melt adhesive composition.
12. 12. The hot melt adhesive composition according to claim 1, wherein the content of the tackifier resin is in the range of 1% by weight to 30% by weight, based on the total weight of the hot melt adhesive composition.
13. The tackifying resin is of the following classes: (a) Natural and modified rosins; (b) glycerol and pentaerythritol esters of natural and modified rosin; (c) the polyterpene resin comprises a hydrogenated polyterpene resin having a Ring and Ball softening point of about 20° C. to 140° C.; (d) phenol-modified terpene resins; (e) Aliphatic (including cycloaliphatic) petroleum hydrocarbon resins (C5) having a Ring and Ball softening point of about 60° C. to 140° C. resulting from the polymerization of C5-hydrocarbon monomers; and the corresponding hydrogenated derivatives resulting from the subsequent total or partial hydrogenation thereof; (f) aromatic petroleum hydrocarbon resins (C9) having a Ring and Ball softening point of about 60° C. to 140° C. resulting from the polymerization of C9-hydrocarbon monomers; and the corresponding hydrogenated derivatives resulting from the subsequent total or partial hydrogenation thereof; (g) aliphatic (including cycloaliphatic) and / or aromatic petroleum resins (C5 / C9) having a Ring and Ball softening point of about 60° C. to 140° C. resulting from the polymerization of C5 / C9 hydrocarbon monomers; and the corresponding hydrogenated derivatives resulting from the subsequent full or partial hydrogenation thereof. The hot melt adhesive composition according to any one of claims 1 to 12, wherein the hot melt adhesive composition is selected from
14. The hot melt adhesive composition according to any one of claims 1 to 13, wherein the (co)polymer B is a copolymer.
15. A hot melt adhesive composition according to any one of claims 1 to 14, characterized in that it is free of polyisobutylene.
16. 16. The hot melt adhesive composition according to any one of the preceding claims, having a Brookfield viscosity in the range of from 1000 mPa.s to 30000 mPa.s measured at 149°C.
17. The hot melt adhesive composition according to any one of claims 1 to 16, wherein the weight ratio of copolymer A:(co)polymer B in the hot melt adhesive composition is in the range of 30:70 to 80:
20.
18. 18. The hot melt adhesive composition according to any one of the preceding claims, having a crystallization enthalpy in the range of from 0.5 J / g to less than 5 J / g.
19. Use of the hot melt adhesive composition according to any one of claims 1 to 18 in hygienic disposable consumer articles, such as diapers, feminine care pads and napkins.
20. 1. A method for producing an assembly (or laminate), comprising the steps of: (i) heating a hot melt adhesive composition as defined in any one of claims 1 to 19 at a temperature in the range of 130°C to 180°C for a time at least long enough to make the hot melt adhesive composition sufficiently liquid for application onto a substrate, then (ii) coating said composition onto a primary substrate, and then - (iii) contacting the coated surface of the primary substrate with a surface of the secondary substrate to form an adhesive bond joining the two substrates. A method comprising:
21. An assembled product comprising at least two substrates bonded by at least one hot melt adhesive composition according to any one of claims 1 to 19.